A Qualitative Analysis of Suicide Ideation among Manitoban Farmers - Sturgeon, Ryan; Morrissette, Patrick J. (Canadian Journal of Counselling and Psychotherapy, 2010)
Canadian studies examining suicide among rural and farm populations remain scarce. To better understand this phenomenon, a qualitative research paradigm was used to analyze encounter forms of 29 individuals (24 men, 5 women) who called the Manitoban Farm and Rural Stress Line. Content analysis revealed 7 major themes: (a) coping mechanisms, (b) financial concerns, (c) health issues, (d) family salvation, (e) uncontrollable events, (f) family stress, and (g) farm culture. Consistent with previous research, it was noted that farmers appear to experience various stressful events, with finances being a key concern. Additionally, farmers report common characteristics not conducive to help-seeking behav-iour. This research indicates a need for increased services specific to Manitoban farmers.